Application of drug-induced sleep endoscopy in infants with dynamic upper airway collapse - Wei, Qing; Yang, Ruimin; Chen, Xun; Yi, Xiang; Liu, Jing; Li, Yan (Frontiers in Pediatrics, 2025)
ObjectiveThe study aimed to evaluate the utility and safety of drug-induced sleep endoscopy (DISE) in infants with suspected dynamic upper airway collapse.MethodsInfants with suspected dynamic upper airway collapse were enrolled in the study. All subjects developed clinical symptoms within the first year of life. Each subject underwent both awake endoscopy (AE) and DISE. Endoscopic findings and sedation strategies for DISE were recorded. The diagnostic rate of dynamic upper airway collapse was compared between the DISE and AE. Adverse events during DISE were also recorded.Results(1) A total of 21 cases were included. The median age at the time of bronchoscopy was 4.0 months. (2) For the cases beyond neonatal age (n = 18), 16 (88.9%) received midazolam only, and 2 (11.1%) received midazolam combined with dexmedetomidine. For the neonates (n = 3), two (66.7%) received 10% chloral hydrate only, and one (33.3%) received 10% chloral hydrate combined with phenobarbital. (3) Six cases (28.6%) were diagnosed under both AE and DISE, whereas 15 cases (71.4%) were diagnosed under DISE only. The diagnostic rate was significantly higher under DISE than that under AE (100.0% vs. 28.6%, P < 0.01) in the cases with dynamic upper airway collapse. Of the cases with laryngomalacia, 3 cases (18.7%) were diagnosed under both AE and DISE, whereas 13 cases (81.3%) were diagnosed under DISE only. The diagnostic rate was significantly higher under DISE than that under AE (100.0% vs. 18.7%, P < 0.01) in the cases with laryngomalacia. Of the cases with tongue base collapse, all (100.0%) were diagnosed under both AE and DISE. Of the cases with retropalatal and hypopharynx collapse, all (100.0%) were diagnosed under DISE only. (4) One case (4.8%) developed a hypoxic episode during DISE, which was resolved by the pressurized facial mask-assisted ventilation.ConclusionsDISE was found to be a feasible and safe procedure in infants with suspected dynamic upper airway collapse. Compared with AE, DISE significantly improved the diagnostic rate of laryngomalacia and appeared to be a more reliable method to diagnose pharyngeal airway collapse, especially retropalatal and hypopharynx collapse.